Unilateral pallidotomy for Parkinson's disease: results after more than 1 year. Issue 4 (1st October 1999) - Schrag, A; Samuel, M; Caputo, E; Scaravilli, T; Troyer, M; Marsden, C D; Thomas, D G T; Lees, A J; Brooks, D J; Quinn, N P
Abstract : OBJECTIVE: To examine follow up results of unilateral ventral medial pallidotomy in 22 patients with advanced Parkinson's disease more than 1 year after the operation in comparison with their results (previously reported) at 3 months. METHODS: Twenty patients who had undergone unilateral pallidotomy were assessed with the core assessment programme for intracerebral transplantation (CAPIT) protocol preoperatively, at 3 months postoperatively, and again after a median postoperative follow up of 14 months. Two further patients had only one evaluation 3 months postoperatively. RESULTS: The reduction of contralateral dyskinesias (median 67%) at 3 months was slightly attenuated after 1 year to 55% (both p<0.001 compared with baseline). A less pronounced effect on ipsilateral and axial dyskinesias decreased from 39% to 33% (p<0.005 and p<0.01), and from 50% to 12.5% (p<0.001 and p<0.01), respectively. However, there was no significant change between the 3 month and the follow up assessment. The modest improvement of the contralateral unified Parkinson's disease rating scale (UPDRS) motor score in the "off" state remained improved compared with preoperative levels, but less significantly (26%, p<0.001, and 18%, p<0.01). The activities of daily living (ADL) subscore of the UPDRS in the off state remained improved with median changes of 23% and 22% at follow up (both p<0.005). There was no significant improvement of "on" state or ipsilateral off state motor scores. Median modified Hoehn and Yahr scores in off and on state were unchanged, as was the time spent off. Speech in off had significantly deteriorated by 1 year after the operation. CONCLUSIONS: The beneficial effects of unilateral pallidotomy persist for at least 12 months and, dyskinesias are most responsive to this procedure.